NILAI EKSPRESIF GRAMATIKA DALAM WACANA KORUPSI DI MEDIA CETAK ‘’FAJAR’’ - Nurlina - Arisnawati (Balai Bahasa Sulawesi Tengah, 2021)
This research aims to describe the expressive value of grammar in the discourse of corruption in the print media